College Student Mental Health and Wellbeing Prior to and during the COVID-19 Pandemic - Margaret McLafferty; Caoimhe Ward; Colum P. Walsh; Siobhan O'Neill; Anthony J. Bjourson; Rachel McHugh; Natasha Brown; Louise McBride; John Brady; Elaine K. Murray (MDPI AG, 2023)
Student mental health was a growing concern globally prior to the onset of the COVID-19 pandemic. The aim of this study was to assess the impact of the pandemic and associated restrictions on the psychological wellbeing of college students. Baseline data were collected pre-pandemic in September 2019 among students attending a university in Northern Ireland and an Institute of Technology in the Republic of Ireland. Surveys were also conducted with this cohort during the pandemic, at the start of the academic years 2020 and 2021 (499 students fully completed all three waves). A follow-up survey was conducted at the end of their third year, in summer 2022 (n = 229). High levels of mental health problems were already present among students commencing college. The subsequent pandemic had a very negative impact on student's academic experience and other aspects of life. Rates of depression (PHQ-9) increased significantly from the onset of the pandemic and remained high. Anxiety (GAD-7) initially decreased but then escalated at the end of college. The study highlights the importance of early intervention and makes recommendations for addressing the needs of students during times of stress. Additional supports may be required to deal with the long-lasting impact of the pandemic.